?-Difference sequence spaces of fuzzy numbers - Altinok, Hifsi; Colak, Rifat; Et, Mikail (Elsevier Science Bv, 2009)
In this paper, using the difference operator of order in and an Orlicz function, we introduce and examine some classes of sequences of fuzzy numbers. We give the relations between the strongly Cesaro type convergence and statistical convergence in these spaces. Furthermore, we study some of their properties like completeness, solidity, symmetricity, etc. We also give some inclusion relations related to these classes. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: Orlicz function; Fuzzy number; Statistical convergence; Difference sequence